Шляхи інтенсифікації видалення зважених речовин зі стічних вод - Кулініч, Сергій Сергійович; Цзі, Х.; Шестопалов, Олексій Валерійович; Босюк, Альона Сергіївна (ГО "Міжнародна наукова гільдія", 2026)
Suspended solids are major pollutants in wastewater, causing turbidity, eutrophication, and reduced efficiency of biological treatment. This study evaluates common removal methods, including mechanical settling, thin-layer sedimentation, coagulation-flocculation (using aluminum sulfate and polyacrylamide), and flotation, showing that combined physicochemical approaches achieve 90–98% suspended solids removal, reducing residual concentrations to 10–25 mg/L.
Keywords: зважені речовини; стічні води; забруднюючі речовини; забруднення стічних вод; евтрофікація; замулювання